2017
DOI: 10.1039/c6pp00453a
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical properties, singlet oxygen generation efficiency and cytotoxic effects of aloe emodin as a blue light photosensitizer for photodynamic therapy in dermatological treatment

Abstract: Conventional photodynamic therapy (PDT) uses red light for deeper penetration. A natural compound, aloe emodin (AE) with anticancer and photosensitising capabilities, excited by blue light, is proposed to treat superficial diseases. The photophysical properties and singlet oxygen quantum yield (Φ) of AE, as well as the cytotoxic effects of AE on human cells, were investigated. The absorption and emission spectra of AE were analyzed. The Φ of AE was measured by a relative method. In order to study the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Although HMME has been approved in China for the photodynamic treatment of naevus flammeus, showing high effectiveness and safety ( Mei et al, 2019 ), it is still not expanded in the photodynamic treatment of bacteria or fungi induced skin diseases. AE is a newly discovered natural anthraquinone PS isolated from Chinese traditional herbs, possessing absorption in the blue region (430 nm) and singlet oxygen quantum yield of 0.57, which may be suitable for the treatment of superficial lesions ( Zang et al, 2017 ). It was reported that AE had low cytotoxicity on epidermis and hypodermal cells and it caused no obvious effects on the weight and pathological changes of mice in our previous study ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although HMME has been approved in China for the photodynamic treatment of naevus flammeus, showing high effectiveness and safety ( Mei et al, 2019 ), it is still not expanded in the photodynamic treatment of bacteria or fungi induced skin diseases. AE is a newly discovered natural anthraquinone PS isolated from Chinese traditional herbs, possessing absorption in the blue region (430 nm) and singlet oxygen quantum yield of 0.57, which may be suitable for the treatment of superficial lesions ( Zang et al, 2017 ). It was reported that AE had low cytotoxicity on epidermis and hypodermal cells and it caused no obvious effects on the weight and pathological changes of mice in our previous study ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous AQs are well-known photosensitizers: Emodin (8), physcion (58), and aloe-Emodin (59), just to name a few examples [4]. 8, 58, and 59 produce singlet oxygen, and thus PDT type II-like activities were proposed [106,107] in combination with PDT type I reactivities [108]. In addition to their wide-spread occurrence in the kingdom Plantae, 8 [109] and 58 [109] are chemotaxonomic markers [110] for mushrooms.…”
Section: Anthraquinones and Perylene Quinonesmentioning
confidence: 99%
“…The mechanisms underlying this effect might be associated with inhibiting the HIF‐1 α /VEGF signaling pathway (Wu et al, ). Zang et al () reported that aloe‐emodin‐mediated PDT may provide an effective strategy for the treatment of superficial diseases using light sources in the blue region, thus protecting deeper normal tissues from PDT‐induced damage (Zang et al, ). Furthermore, aloe‐emodin could induce the synthesis of matrix proteoglycans, increase the activity of ALP, and enhance the expressions of chondrogenic marker genes such as Collagen II, Collagen X, bone sialoprotein, and runt‐related transcription factor 2 via MAPK and bone morphogenetic protein‐2 signaling pathways, indicating aloe‐emodin may have potential future applications for the treatment of growth disorders (Yang, Li, Heo, & Soh, ).…”
Section: Pharmacologymentioning
confidence: 99%